Efficacy of a Phosphate-Charged Soil Material in Supplying Phosphate for Plant Growth in Soilless Root Media - Young-Mi Oh; Paul V. Nelson; Dean L. Hesterberg; Carl E. Niedziela (International Journal of Agronomy)
A soil material high in crystalline Fe hydrous oxides and noncrystalline Al hydrous oxides collected from the Bw horizon of a Hemcross soil containing allophane from the state of Oregon was charged with phosphate-P at rates of 0, 2.2, and 6.5 mg·g−1, added to a soilless root medium at 5% and 10% by volume, and evaluated for its potential to supply phosphate at a low, stable concentration during 14 weeks of tomato (Solanum esculentum L.) seedling growth. Incorporation of the soil material improved pH stability, whether it was charged with phosphate or not. Bulk solution phosphate-P concentrations in the range of 0.13 to 0.34 mg·dm−3 were associated with P deficiency. The only treatment that sustained an adequate bulk solution concentration of phosphate-P above 0.34 mg·dm−3 for the 14 weeks of testing contained 10% soil material charged with 6.5 mg·g−1 P, but initial dissolved P concentrations were too high (>5 mg·g−1 phosphate-P) from the standpoint of phosphate leaching. The treatment amended with 10% soil material charged with 2.2 mg·g−1 P maintained phosphate-P within an acceptable range of 0.4 to 2.3 mg·dm−3 for 48 d in a medium receiving no postplant phosphate fertilization.